Pengaruh Pemberian Terapi Relaksasi dan Brain Gym Terhadap Jumlah Hafalan Al-Qur'an Santriwati Pondok Pesantren Tahfizhul Qur'an Daarul Qur'an Colomadu - Nairoh, Ulfiatun; , Isnaini Herawati, S.Fis, S.Pd, M.Sc; , Totok Budi Santoso , S.Fis , MPH (2017)
ABSTRACT PHYSIO THERAPY DEPARTEMENT HEALTH SCIENCE FACULTY MUHAMMADIYAH UNIVERSITY OF SURAKARTA MINITHESIS, MARCH 2017 ULFIATUN NAIROH/ J 120 130 020 "THE INFLUENCE OF RELAXATION THERAPY AND BRAIN GYM TOWARD NUMBER OF STUDENT'S AL-QUR'AN MEMORIZING AT PONDOK PESANTREN TAHFIZHUL QUR'AN DAARUL QUR'AN COLOMADU" V CHAPTERS, 50 Pages, 1 Table Dan 3 Schemes. (Counseled by: Isnaini Herawati, S.Fis., S.Pd., M.Sc) Background: Indonesia has the biggest number and potential of Al-Qur'an's memorizing people in the world. There many Al-Qur'an boarding schools are built. The matter of student's Al-Qur'an memorizing are bored and surfeited that hamper the process of Al-Qur'an memorizing. In addition, more activities in the Al-Qur'an boarding school causes physical weakness and stress which influence decreasing the level of focus skill and memory that needed on memorizing process. The extending of relaxation therapy and brain gym have a purpose to return the student's composure, conscious and well focusing. Research Aims: To determine the influence of relaxation therapy and brain gym toward number of student's Al-Qur'an memorizing at Pondok Pesantren Tahfizhul Qur'an Daarul Qur'an Sanggir, Paulan, Colomadu, Karanganyar. Researh Method: The kind of this research is Quasi Experimental Design with the research design is Equivalent Times Sample Design. The sampling technique used is Purposive Sampling. Total sample is 18 samples. Results: The result of Wilcoxon test explain increasing the number of Al-Qur'an memorizing average in the amount of 0,8 with p value 0,019. Conclusion: Relaxation therapy and brain gym have an effect toward the number of student's Al-Qur'an memorizing Pondok Pesantren Tahfizhul Qur'an Daarul Qur'an Colomadu. Keywords: Relaxation, Brain Gym, Memorized Al-Qur'an.